2019
DOI: 10.3389/fcell.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Oxidation Promotes Cardiomyocyte Proliferation Rate but Does Not Change Cardiomyocyte Number in Infant Mice

Abstract: Cardiomyocyte proliferation accounts for the increase of cardiac muscle during fetal mammalian heart development. Shortly after birth, cardiomyocyte transits from hyperplasia to hypertrophic growth. Here, we have investigated the role of fatty acid β-oxidation in cardiomyocyte proliferation and hypertrophic growth during early postnatal life in mice. A transient wave of increased cell cycle activity of cardiomyocyte was observed between postnatal day 3 and 5, that proceeded as cardiomyocyte hypertrophic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 45 publications
4
43
0
Order By: Relevance
“…Heart ventricles were harvested 24 hours after the last injection. Previous studies demonstrated the expression of fatty acid metabolismassociated genes (Acaca, Acacb, Acadl, Acadm, Cpt1b) as indicators of PPARα biological activity in vivo [21]. Consistent with these previous studies, GW7647 treatment resulted in a significant increase in the mRNA level of these genes ( Figure 1B).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Heart ventricles were harvested 24 hours after the last injection. Previous studies demonstrated the expression of fatty acid metabolismassociated genes (Acaca, Acacb, Acadl, Acadm, Cpt1b) as indicators of PPARα biological activity in vivo [21]. Consistent with these previous studies, GW7647 treatment resulted in a significant increase in the mRNA level of these genes ( Figure 1B).…”
Section: Resultssupporting
confidence: 89%
“…However, ETO treatment led to significant lower levels of EF and FS compared with the saline treatment ( Figure 2D). Our previous studies have suggested that ETO treatment prevented cardiomyocyte maturation in early postnatal mouse hearts [21].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations